IJCM_395A: Exploring medical student's perspective on Competency based medical education (CBME) curriculum at Government Medical College in Maharashtra. - Pujitha Ananthaneni Sai; Inamdar I. F; Gattani P.L; Maidapwad S.L; Gadekar R.D (Wolters Kluwer Medknow Publications, 2024)
Background: Competency based medical education (CBME) is implemented recently in India. The study was conducted to evaluate the perspectives of undergraduate medical students towards CBME curriculum at a Government Medical College in Maharashtra. CBME is helpful in expanding the dimensions besides basic medical knowledge to the core competencies of a high-grade skilled clinical graduate. Moreover, value addition with other competencies such as empathy, professionalism, altruism, communication skills, ethics, and humanities that focuses on health systems as a National goal 'Health for All'. Objective: To explore medical student's perspective on Competency based medical education (CBME) curriculum at Government Medical College in Maharashtra. Methodology: This cross-sectional descriptive study was conducted among undergraduate medical students at Dr. SCGMC, Nanded. A validated questionnaire was administered through Google link among medical students. Results: A total of 225 students has participated. Around 130 (58%) students are from first year and 96(43.2%) students opined that learning AETCOM skills are necessary and around 125(55.8%) students opined that there should be sometime for sports activities during week days also and 107(48.2%) students stated that early clinical exposure in the first year is beneficial. Conclusion: The CBME curriculum focuses on learning the competencies needed in clinical practice and provides standards and framework for measuring performance. The thrust of the new curriculum attempts to make medical education in India more outcomes oriented.